Anak Jakarta; A sketch of Indonesian youth identity - Sarwono, Solita (UI Scholars Hub, 2014)
Anak Jakarta refers to the youth of Jakarta, the trend-setters of the Indonesian youth. This paper gives a sketch of the youth in Jakarta as characterized by their appearance, language and lifestyle. Information is derived from discussions and personal contact with different groups of youth and parents (adults with children) in Jakarta; literature review, observations, as well as from flashbacks given by the adults, providing a portrait of anak Jakarta since late 1980's. The youth in Jakarta is Western (American) oriented, copying from the mass- and social media, often times conflicting with local norms and parental advices. Anak Jakarta profile includes: youth created slang language, school gang fights (tawuran) and brand minded consumerism. Jakarta youth has become the role model for most youth all over Indonesia, especially Jakarta migrant youth. Family upbringing, social contact, peer group and the media play a crucial role in forming, transforming and disseminating the characteristics anak Jakarta identity.